2010
DOI: 10.1007/s00267-010-9554-7
|View full text |Cite
|
Sign up to set email alerts
|

Marine Protected Dramas: The Flaws of the Brazilian National System of Marine Protected Areas

Abstract: This article discusses the current problems and issues associated with the implementation of a National System of Marine Protected Areas in Brazil. MPA managers and higher governmental level authorities were interviewed about their perceptions of the implementation of a national MPA strategy and the recent changes in the institutional arrangement of government marine conservation agencies. Interviewees' narratives were generally pessimistic and the National System was perceived as weak, with few recognizable m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(66 citation statements)
references
References 16 publications
0
60
0
6
Order By: Relevance
“…Due to the lack of planning and enforcement, it is easy to find many illegal activities within these areas (Sá & Ferreira 1999). For example, several shrimp farms can be found within many EPAs in the Northeast, frequently making them appear as 'paper parks' (Boeckmann & Geber 2006;Gerhardinger et al 2010). In addition, it is easier to enforce a fully protected marine reserve (no-take zone) than 'partially' protected areas, the latter being sometimes no better than areas without regulations.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of planning and enforcement, it is easy to find many illegal activities within these areas (Sá & Ferreira 1999). For example, several shrimp farms can be found within many EPAs in the Northeast, frequently making them appear as 'paper parks' (Boeckmann & Geber 2006;Gerhardinger et al 2010). In addition, it is easier to enforce a fully protected marine reserve (no-take zone) than 'partially' protected areas, the latter being sometimes no better than areas without regulations.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of addressing existing issues in the network system, the designation of more marine protected areas, in the way it is currently taking place in Brazil, could actually decrease implementation capacity and effectiveness, not achieving much beyond the fulfillment of the country's internationally established marine biodiversity targets (Gerhardinger et al, 2011). Plus, a national effectiveness monitoring scheme still lacks for marine protected areas, even though Brazil has a large number of scientists and other professional capable of performing or assisting with such a task.…”
Section: Assessment Of the Protected Area Systemmentioning
confidence: 99%
“…Having such results as a starting point, this agency could synthesize data produced and evaluate what information is missing, which could then be used in conservation studies. Plus, systemic and interdisciplinary studies, which include not only ecological, but also social, political and economic aspects, can provide the solution to complex problems faced by Brazilian marine protected areas (Gerhardinger et al, 2011).…”
Section: Standardized Gis-based Information and Synthesis Workmentioning
confidence: 99%
“…Participation improves the legitimacy of MPA agreements, implementation, and enforcement, particularly across sovereign borders (Leenhardt et al 2013). Policy actors can constrain financial resources, and administrative and legal capacities, severely limiting implementation (Ferraro et al 2011;Gerhardinger et al 2011;Jentoft et al 2012;Ramirez 2016;Sandstr€ om et al 2016). These problems highlight the importance of understanding how to improvise and adapt policy to be responsive to diverse conservation needs, stakeholder contexts, and to overcome multiple and diverse governance barriers limiting action across large sites.…”
Section: Governance Lessons From the Mpa Experiencementioning
confidence: 99%
“…The blanket application of MPA tools to large marine sites is also highly problematic. Though the blanket application of MPA tools may give the impression that conservation targets have been achieved (i.e., to have 10% or 20% of marine waters covered by a protected area), it does not lead to long-term marine conservation outcomes (Gerhardinger et al 2011;Agardy, Claudet, and Day 2016). In smaller MPAs, experience has shown that poorly contextualized policy creates its own problems.…”
mentioning
confidence: 99%